Insights into spatial inhomogeneity in an oxygen plasma from cavity ringdown spectroscopy - Rogers, SDA; Bond, A; Peverall, R; Hancock, G; Ritchie, GAD (IOP Publishing, 2024)
Cavity ringdown spectroscopy has been used to investigate the translational and rotational temperatures of the v = 0 and 1 vibrational levels of O2(X) in an inductively coupled plasma at 100 mTorr (13.332 Pa) pressure. All rotational states probed display a clear increase in temperature as plasma power increases: at fixed power, the translational temperature appears largest for rotational states in v = 1 (J= 7, 16, 17, 22) and lowest in the low energy states (J = 1, 18, 19) in v = 0; highly excited rotational states (J = 28, 30, 31) of v = 0 show intermediate behaviour. The rotational temperature values behave similarly. These observations are consistent with the effects of plasma inhomogeneity and can be interpreted with a simple one-dimensional model whereby the pressure, temperature and mole fractions of the various species across the chamber (and arms) are approximated with rational profiles and the corresponding line-of-sight averaged densities and temperatures calculated. This basic model is reasonably successful at reproducing the observations for O2(X, v = 0) and O(3P) densities. The fact that resolving several rotational transitions allows spatial variations within the plasma to be inferred from line-of-sight averaged measurements is an extremely powerful result that could be of great utility in future work.